2016
DOI: 10.2116/analsci.32.763
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Fluorescence Methods for the Determination of Alfuzosin, Doxazosin, Terazosin and Prazosin in Pharmaceutical Formulations, Plasma and Urine

Abstract: Polymeric ionic liquid-coated magnetic nanoparticles have been successfully prepared as adsorbents for the magnetic solid-phase extraction of four drugs, namely alfuzosin, doxazosin, terazosin and prazosin, from pharmaceutical preparations, urine samples and plasma samples. The four drugs were detected by fluorescence spectrophotometer. Several extraction parameters, including the pH of the solution; the type, ratio and volume of the desorbing reagent; the amount of adsorbent; the time of the extraction and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…ILs are also used in analytical chemistry, including electroanalytical chemistry 2,3 and separation chemistry. [4][5][6][7] Solvent extraction of metal cations is a separation technique using large amounts of hydrophobic organic solvents for the extraction phase materials.…”
Section: Introductionmentioning
confidence: 99%
“…ILs are also used in analytical chemistry, including electroanalytical chemistry 2,3 and separation chemistry. [4][5][6][7] Solvent extraction of metal cations is a separation technique using large amounts of hydrophobic organic solvents for the extraction phase materials.…”
Section: Introductionmentioning
confidence: 99%
“…The complete process took 42 h, without considering the time for washing and purication steps. Other authors 27,30 have reported similar reaction times, temperatures and inert atmosphere to obtain the nal PIL magnetic nanocomposite.…”
Section: Introductionmentioning
confidence: 75%
“…The desorption of our target analyte from the surface of the SDS-coated MNPs can be obtained by adding organic solvents as reported in previous works [ 24 , 27 , 28 , 29 ]. It was found that organic solvents can disrupt the formed hemimicelles/admicelles, which diminishes the available place for GEF adsorption.…”
Section: Resultsmentioning
confidence: 99%